A Mixed Methods Framework for Evaluating Synergies Between Shared Contact Centres, Organisational Performance, and Customer Service in Eastern Cape, South Africa (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The proliferation of Shared Contact Centre Services (SCCs) across public and private sectors in the Eastern Cape reflects a broader global trend toward centralized service delivery. However, the conceptual underpinnings of SCCs particularly in relation to synergy, competitive advantage, and definitional precision remain underexplored. This study examines the synergistic interface between SCCs and organisational business units, with a focus on their collective impact on organisational performance, strategic competitiveness, and customer service within the Eastern Cape Provincial Administration. Anchored in the Attention-Based View (ABV) and informed by synergy theory, the research adopts a sequential Mixed Methods Research (MMR) design. A qualitative constructionist methodology enabled the co-creation of contextual insights, while quantitative analysis facilitated triangulation, enhancing the reliability and generalisability of findings across South African provincial contexts. The study culminated in the development of a multidimensional conceptual framework for evaluating synergy, structured around six core dimensions: strategic alignment, process integration, technological enablement, performance metrics, customer centricity, and continuous improvement. The empirical findings demonstrated that the proposed framework significantly enhances interdepartmental collaboration, communication, and knowledge exchange, thereby improving productivity, employee engagement, and organisational health. Furthermore, the framework contributes to elevated customer satisfaction, loyalty, and retention factors that collectively drive revenue growth and market expansion. By mitigating operational silos and fostering strategic coherence, the framework enables organisations to systematically assess SCC performance, identify areas for optimisation, and align service delivery with overarching corporate strategy to maximise customer value.